Pemanfaatan Teknologi Informasi dalam Negosiasi dan Komunikasi Bisnis: Analisis Deskriptif Berbasis Studi Pustaka (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Developments in information technology have had a significant impact on business communication and negotiation processes in various industrial sectors. Technological advances such as email, video conferencing, instant messaging applications, cloud-based information systems, and other digital media have created new, faster, more efficient, and more documented communication models. This study uses a descriptive approach based on a literature review to analyze how information technology is transforming interaction patterns, strategies, and negotiation processes in the modern business environment. The results indicate that information technology plays a strategic role in increasing the effectiveness of business communication and accelerating the negotiation process. Advantages such as cost savings, time flexibility, global access, and automated documentation are the main reasons for the increasing use of digital media in the business world. However, digital negotiation also presents challenges such as the loss of non-verbal context, the risk of miscommunication, data security issues, and limitations in interpersonal relationships. The conclusion of this study confirms that successful negotiations in the digital era are greatly influenced by interpersonal communication skills, digital literacy, appropriate media selection, and the implementation of negotiation strategies that adapt to technological changes.